Subtitution Leaf Fermentation Leucaena (Leucaena leucocephala) on Feed vaname shrimp (Litopenaeus vannamei) for Retention of Protein and Energy - Rheza Ariyandra; Agustono .; Woro Hastuti Satyantini (Journal of Aquaculture Science, 2017)
Intensive aquaculture systems causing heavy reliance on the use of artificial feed (Heptarina et al., 2010). Feed is a crucial component to the success of shrimp farming (Soemardjati and Suriawan, 2006). According to Haryanto and Djajanegara (1993) lamtoro leaves contain protein, calcium and energy. The content of the leaves lamtoro a source of protein for feed ingredients in this plant are essential amino acids lysine and leucine were very high (D'Mello and Fraser, 1981). The consideration for the selection of feed materials should be done in accordance with the provisions of the feed material that is readily available, low cost, high nutrient content and do not compete with humans (Handajani et al., 2010). According to Matthew (1993), leucaena as forage quality has not been used optimally and not much commercialized. Lamtoro a potential biological resources to be used as feed to the waste generated sufficient forage nutritional value (Widiastuti, 2007). Research on the use of fermented flour substitution lamtoro leaf is a matter that needs to be done because of the use of fermented flour lamtoro leaf is expected to improve the quality of feed and make it as an alternative feed ingredient that can be given to increase aquaculture production. This research is the experimental method using a completely randomized design (CRD) with four treatments and five replications. The results of this study will be analyzed descriptively in the form of data and tables. Data obtained, processed using Analysis of Variance (ANOVA) to determine the effect of different treatments applied if real, then continued with Duncan's Multiple Range Test (Duncan's Multiple Range Test) with a 5% error rate to determine the best treatment.   Keywords: Feed, Vaname Shrimp, Fermentation, Substitution, Leucaena Leaf, Protein Retention, Retention Energy.